Experimental evidence for anti-metastatic actions of apigenin: a mini review - Oh, Hyeon-Muk; Cho, Chong-Kwan; Lee, Nam-Hun; Son, Chang-Gue (Frontiers in Oncology, 2024)
Cancer metastasis is responsible for the majority of cancer-related deaths. Accordingly, to reduce metastasis remains a vital challenge in clinical practice, and phytochemicals have taken an attention as anti-metastatic agents. Apigenin, a plant flavone, showed anti-cancer effects against in various animal models, moreover its potentials inhibiting tumor metastasis have been reported. Herein, we analyzed the overall features at what apigenin inhibited metastasis and its action modes. We searched for articles in MEDLINE (Pubmed), EMBASE and Cochrane Central Register of Controlled Trials (CENTRAL) through March 2023. Total 6 animal studies presented anti-metastatic effects of apigenin using 5 difference experimental models, while the mechanisms involved modulations of epithelialmesenchymal transition (EMT), matrix metalloproteinases (MMPs), angiogenesis, and various metastasis-related signaling pathways. This review provides an overall potential of apigenin as a candidate reducing the risk of cancer metastasis.